DEVELOPMENT OF SEEDS INDUSTRY OF CASHEW - YULIUS FERRY (Perspektif, 2012)
Cashew (Anacardium occidentale L.) is very important to the economy of communities in marginal areas, such as provinces of NTT, NTB, South Sulawesi, and Southeast Sulawesi. Demand of cashew keeps increasing, however, crop productivity is still low so that the production and farmers' income are not optimal yet. Low crop productivity is caused partly by old plant age, random seeds usage, and in-appropriate application of cultivation techniques. To increase production and productivity of the cashew nationally, Directorate General of Estate Plantation has developed a road map for development and rejuvenation of cashew crop until the year 2025, with an average area of 213,430 ha/year. Replanting development will require as many as 32,014,500 seed stems/year. High Producing Blocks are only capable of providing seed as much as 4.69% of the total need, while to cover the rest, it is required to construct 823.7 ha of plantation master. Parent garden can be built in areas of development centers, in the form of the parent composite garden consisting of 3-4 superior varieties. Area per farm holding should be not less than 100 ha or in accordance with the scale of the effort to stem the garden. Keynotes: Cashew (Anacardium occidentale L.), seed, superior variety, development